Identification and expression of cysteine sulfite decarboxylase genes and their response to hyposalinity stress in Ruditapes philippinarum - Zhang, Zhichao; Wang, Jun; Huo, Zhongming; Nie, Hongtao; Yan, Xiwu; Ding, Jianfeng (Frontiers in Marine Science, 2023)
Cysteine sulfinate decarboxylase (CSAD) is a rate-limiting enzyme in taurine biosynthesis. In this study, the structure and expression characteristics of the RpCSAD gene in Ruditapes philippinarum were analyzed. The pyridoxal phosphate (PLP)-dependent amino acid carboxylase structural domains and catalytic active sites of six copies of RpCSAD were highly conserved. Tissue expression analysis demonstrated that RpCSAD1 and RpCSAD3-6 was primarily expressed in the mantle tissue, and RpCSAD2 in the water tube and gonad tissue. After exposure to hyposalinity stress, the expression levels of RpCSADs were found to be upregulated in all three shell-colored groups of clams. Remarkably, there was a pronounced increase in the expression of RpCSAD1-6 observed specifically in the zebra shell-color groups. These findings strongly suggest the involvement of taurine metabolism in the response of zebra shell-color clams to low salinity stress, thereby emphasizing its critical role in the adaptation mechanisms. These findings could contribute to a better understanding the mechanisms of osmotic stress tolerance in shellfish.